2014
DOI: 10.1007/s13204-014-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical and impedance studies of pure and Ba-doped ZnS quantum dots

Abstract: Chemical precipitation method using a highboiling solvent is used to synthesize ZnS and Ba-doped ZnS quantum dots. The presence of organic ligands in the prepared nanostructures is verified using Fourier transform infra-red spectroscopic studies. The samples have been analysed using X-ray diffraction analysis confirming nanocrystallinity of the as-prepared quantum dots (QD). The mean crystal size obtained by full width half maxima analysis is 3.2 nm for ZnS and 3.9, 4.2 nm for ZnS:Ba (2, 4 mM). TEM micrographs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…7b. The energy gap of pure ZnS from literature is found to be 3.67 eV at ambient temperature [70]. The energy gap of Mn = 3% doped ZnS (Zn 0.97 Mn 0.03 S) obtained from Fig.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 88%
“…7b. The energy gap of pure ZnS from literature is found to be 3.67 eV at ambient temperature [70]. The energy gap of Mn = 3% doped ZnS (Zn 0.97 Mn 0.03 S) obtained from Fig.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 88%
“…According to the optical analysis, ZnS and Ba-doped ZnS (2, 4 mM) nanocrystals have energy gaps of 4.88 eV and 4.69, 4.43 eV, respectively. 75…”
Section: Nitrogen (N)-doped Znsmentioning
confidence: 99%
“…Firdous, Singh et al fabricated ZnS QDs and barium-doped ZnS QDs (ZnS/Ba QDs) with chemical precipitation to study their optical and electrical properties. They found that the bandgap of ZnS/Ba QDs decreased from 4.88 eV to 4.43 eV with the introduction of Ba into ZnS QDs [23]. Jabeen, Pathak et al synthesized ZnS QDs, silver-doped ZnS QDs (ZnS/Ag QDs) and gold-doped ZnS QDs (ZnS/Au QDs) with chemical method.…”
Section: Dopingmentioning
confidence: 99%